Loading of Fe/Al compounds and adsorption of vanadium (V) on diatomite from Changbai Mountain. Issue 197 (24th March 2019) - Ju, Li; Zhang, Peicong; Huang, Yi; Ni, Shijun; Li, Junfeng; Qiu, Kehui; Shen, Bolin; Wang, Tian; Gao, Qing
Abstract: In this study, the loaded diatomite was prepared with Changbai Mountain diatomite as the carrier according to different Fe/Al molar ratios. The structure and adsorption of the above materials were characterized by XRD, SEM, and ICP-OES. The effects of Fe/Al molar ratio, adsorption time, initial concentration of V(V), and the initial pH value of the solution on the adsorption performance of loaded diatomite were explored. The diatomite loaded with Fe/Al compounds could significantly improve the removal efficiency of V(V), and the removal efficiency of loaded diatomite prepared according to a Fe/Al molar ratio of 1:3 was better. Reaction equilibrium time is 24 h and the pseudo second-order kinetic equation can better describe the adsorption kinetic behavior of V(V) on loaded diatomite. When the initial concentration of V(V) increased from 15.85 mg/L to 122.5 mg/L, the unit adsorption capacity and removal rate of V(V) by loaded diatomite increased continuously. The adsorption behavior of V(V) on loaded diatomaceous earth belongs to the chemical adsorption via the multi-molecular layer, which is consistent with the Freundlich isotherm adsorption model. A weak acid environment is beneficial to the adsorption behavior of V(V) on loaded diatomaceous earth and the strong alkaline environment should be avoided.